The Role of Self-Efficacy and Religiosity in Determining Female Teachers' Resilience - Marisa, Siti; Daulay, Nurussakinah; Darmayanti, Nefi; Shakirah Mat Akhir, Noor (Universitas Muhammadiyah Yogyakarta, 2024)
Resilience is a crucial element in helping teachers manage various pressures and demands stemming from dual roles as educators and homemakers. This study aims to examine the influence of self-efficacy and religiosity on resilience, as well as to test the moderating role of religiosity in the relationship between self-efficacy and resilience. The study involved 167 female teachers from state madrasahs in Medan City as respondents. Data collection was conducted through a survey using online questionnaires employing three measurement tools: the General Self-Efficacy Scale (GSES), the Short Muslim Belief and Practice Scale (Short-MPBS), and the Connor-Davidson Resilience Scale-25 (CD-RISC-25). Data analysis was carried out using Structural Equation Modeling (SEM). This research offers novel insights into understanding resilience among female madrasah teachers by introducing religiosity as a moderating variable. The findings indicated that: 1) there is a positive relationship between self-efficacy, religiosity, and resilience; 2) religiosity does not moderate the relationship between self-efficacy and resilience. This study reveals that although religiosity serves as spiritual support, the dominance of self-efficacy highlights the importance of tangible actions in overcoming challenges. The study underscores the significance of building self-efficacy and provides new insights into developing support strategies for female madrasah teachers. Field data support the hypotheses.